Investigation of the shear behavior of RC beams on the basis of measured crack kinematics. (15th April 2016) - Huber, Patrick; Huber, Tobias; Kollegger, Johann
Highlights: A test series on twenty reinforced concrete beams is presented. Kinematics of the diagonal crack is investigated by using digital image correlation. Measured kinematics is used to estimate the various shear transfer actions. The importance of aggregate interlock is shown. An explanation for the size effect and the influence of the presence of flanges is given. Abstract: This paper deals with an experimental and theoretical assessment of the shear strength of reinforced concrete beams with and without a minimum amount of transverse reinforcement. Various shear transfer mechanisms contribute to the shear strength. The contributions of aggregate interlock, residual tensile stresses at the crack tip, dowel action, and shear strength of the shear reinforcement depend mainly on the opening and sliding behavior of the critical shear crack, which is directly linked to its shape. In this paper, the kinematics of the diagonal crack is investigated in 20 test specimens by using three-dimensional digital image correlation. In this test series the influences of the member depth, the cross section, the type of concrete, and a minimum amount of transverse shear reinforcement on the shear behavior are investigated. Based on the full-field optical measurements and the use of different constitutive laws from literature an estimation of the contributions of the various shear transfer mechanisms is performed. Further, an evaluation of their impact on the shear strength at failure including the influences of the investigated parameters is carried out. An explanation for the pronounced size effect for beams without any transverse reinforcement is given. Moreover, the importance of aggregate interlock as well as the effect of the presence of flanges for beams with and without stirrups is shown. A comparison of the experimental results with the sum of the contributions to the shear strength by each mechanism (based on the measured crack kinematics) yields reasonable agreement.